Liquid Crystals: Tunable Gas Sensing Gels by Cooperative Assembly (Adv. Funct. Mater. 27/2017). (17th July 2017) - Hussain, Abid; Semeano, Ana T. S.; Palma, Susana I. C. J.; Pina, Ana S.; Almeida, José; Medrado, Bárbara F.; Pádua, Ana C. C. S.; Carvalho, Ana L.; Dionísio, Madalena; Li, Rosamaria W. C.; Gamboa, Hugo; Ulijn, Rein V.; et al.
Abstract : Jonas Gruber, Ana C. A. Roque, and co‐workers report a tunable gas‐sensing gel in article number1700803 . The gel is generated by cooperative self‐assembly of liquid crystals, biopolymers, and ionic liquid. Thin films react to stimuli by generating optical and electrical signals. Compared to metal oxide semiconductor based gas sensors, the system is more stable, operates at low temperatures and can be prepared without toxic material.